The Influence of Packaging and Information Transparency on Intention to Try with Endorser Capability as Moderation - Auditia Setiobudi; Deandra Vidyanata; Clarissa Sabella (Fakultas Bisnis, 2021)
Food and beverage industry is growing rapidly which causes companies to trying to fullfil consumer needs, one of which is packaging. Packaging is an important element to protect the product. Technological advances are able to make it easier for everyone to get information. Transparency information is able to provide information that consumers need. The purpose of this research is to examine the effect of packaging and information transparency on the intention to try Cikake products and to examine the moderating effect of endorser capability between information transparency on intention to try Cikake's. The population of this research is Cikake consumers who have tried this product before, have an Instagram account and live around the city of Pandaan. The sampling method used in this study was the census method, with a population of 100 people as the sample. Respondent data is collected by distributing questionnaires to Cikake consumers. This research uses Moderated Multiple Regression (MMR) as an analysis tool. The finding from the results of multiple linear regression tests which resulted in a significance value on the packaging variable of 0.005 while the information transparency variable was 0.000, which means that packaging and information transparency had an effect on the intention to try. The effect of moderation has a significance value of 0.030 and an increase in the coefficient of determination, which means that endorser capability is able to moderate the relationship of information transparency to intention to try Cikake's.